The Relationship of School Climate and Parental Involvement in Children’s Education: A Research Review - Maša Đurišić; Mila Bunijevac; Nataša Duhanaj (Društvene i Humanističke Studije, 2023)
Although there is no generally accepted definition of school climate and a single position on its dimensions, most authors agree that school climate is a multidimensional and complex construct, which refers to the quality and character of school life. Although the available empirical literature abounds with evidence of the effects of school climate on academic and psychosocial outcomes of education, this relationship continues to occupy the attention of researchers. This paper provides an overview of recent research on this issue with the aim of determining the connection between the key dimensions of the school climate (academic, social and physical) and parental involvement in children’s education. Review and analysis of electronically available literature was performed according to appropriate criteria. After the literature review, the ten most influential research studies were selected for analysis. The most important results of the studies included in the analysis are: between school climate and parental involvement there is a positive connection of moderate to strong intensity; all three dimensions of school climate are significantly related to parental involvement; ethnicity and school size influence the strength of the relationship between school climate and parental involvement. Based on the presented empirical findings, it can be concluded that the school climate is important for improving the cooperation between the family and the school. Accordingly, recommendations for future research and practice are given.